Pengaruh Latihan Kognitif terhadap Perubahan Skor Fungsi Kognitif pada Lansia dengan Dimensia Ringan di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin: The Effect of Cognitive Training on Changes in Cognitive Function Scores in Elderly Individuals with Mild Dementia at Tresna Werdha Sabai Nan Aluih Sicincin Social Home - Ihda Al Adawiyah MZ; Heppi Sasmita; Miswarti (Fakultas Keperawatan Universitas Andalas, 2012)
The purpose of this research was to see Cognitive exrecise effetc towards cognitive function increase on the old peoplewith light dimentia at PSTW Sabai Nan Aluih Sicincin 2012. The research was Quasi-Eksperiment-designed with two group pretest-post test design which consist of 2 group, group of experiment and group of control. The researched took place at PSTWSabai Nan Aluih Sicincin from January untill May 2012. Research sample was taken with purposive sampling methode consist of 34 peoples, 17 peoples of experimenting group and 17 peoples of controling group. The measurement of cognitive function was taken with MMSE (Mini Mental State Examantion). Statistic analysis was computerized with Paired t-test examination. There was significant relation in the results of this research between cognitive exercise with cognitive function score alteration with average score change 4,23 and there was score decrease on controlling group with average value -1,53. From the result of Paired t-test examination was obtained p value of 0,019 (p < 0,05). From those result of the research,it can be expected that PSTW Sabai Nan Aluih Sicincin can aplly cognitive exercise (brain gym) on The old people and become an alternate event program to increase the prosperity of the old people.